Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have equation of type: $$ a x^2 y(x)'' + bxy(x)' + cy = d(x) $$ it is called, in my text book, a second order Euler equation. They say that I need to put $e^t$ instead of $x$ and than $Y(x(t))=y(x)$

After this, they write that it is clear that: $$\begin{align} x\frac{dy}{dx}&=\frac{dY}{dt}\\ (x^2)y'' &= \frac{d^2Y}{dt^2}-\frac{dY}{dt} \end{align} $$ Please tell me what are they doing here.


share|cite|improve this question
can you tell us the name of the book and the page ? or can you provide the full text? – user13838 Oct 8 '11 at 8:50
Also this has the full derivation. – user13838 Oct 8 '11 at 8:51
the book is in Hebrew. – Nahum Litvin Oct 8 '11 at 8:52
@percusse I found this link as well but I cannot understand how to use this in an exam. – Nahum Litvin Oct 8 '11 at 8:53
in the link I provided, equation number (8) to (11), is the variable substitution $e^z=x$ or $z=\ln x$. You can use this in an exam if you know how to solve the resulting second order diff. eq. with constant coefficients. – user13838 Oct 8 '11 at 9:14
up vote 1 down vote accepted

It's clear that $$\frac{dx}{dt} = x.$$

Using the chain rule on $Y(x(t))$, this implies that

$$\frac{dY}{dt} = \frac{dy}{dx}\frac{dx}{dt} = x \frac{dy}{dx}.$$

You now derive once more with respect to $t$:

$$\begin{align}\frac{d^2Y}{dt^2} &= \frac{dx}{dt} \frac{dy}{dx} + x \frac{d}{dt}\frac{dy(x(t))}{dx}.\\ &= x \frac{dy}{dx} + x \frac{d^2y}{dx^2} \frac{dx}{dt}\\ &= \frac{dY}{dt} + x^2 y^{''}(x). \end{align}$$

share|cite|improve this answer

I don't know what are they doing but I know that for Euler differential equation we can make substitution $x=e^t$, and after that we can write following:

$x'_t=(e^t)'_t \Rightarrow \frac{dx}{dt}=e^t \Rightarrow dx=e^tdt$

Since we know that $y'_x=\frac{dy}{dx}$ ,we can write:


Similarly we can show that:


Now if you substitute these expressions into ODE you will get:

$ay''_t+(b-a)y'_t+cy=d(t)$, which can be solved if we first solve homogeneous equation:


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.